Hasil Belajar Ekonomi di Era Digital: Peran Literasi Digital, Kolaborasi Teman Sebaya, dan Self-Regulated Learning - Elfonda; Muazza; Rosmiati (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the effects of digital literacy, peer collaboration, and self-regulated learning on the Economics learning outcomes of senior high school students. The study employed a quantitative explanatory approach using a cross-sectional survey design. The population consisted of 180 students, from which a sample of 124 students was selected through simple random sampling. Data on digital literacy, peer collaboration, and self-regulated learning were collected using questionnaires, while data on Economics learning outcomes were obtained from school academic records. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) with the assistance of SmartPLS. The results showed that digital literacy had a positive and significant effect on Economics learning outcomes (β = 0.443, p < .001). Peer collaboration also demonstrated a positive and significant effect on Economics learning outcomes (β = 0.406, p < .001). In addition, self-regulated learning had a positive and significant effect on Economics learning outcomes (β = 0.122, p = .033). The model explained 62.8% of the variance in Economics learning outcomes (R² = 0.628), indicating moderate explanatory power. These findings suggest that students’ Economics learning outcomes are influenced by their ability to utilize digital learning resources effectively, engage in meaningful academic interaction with peers, and regulate their learning processes independently. Based on these findings, Economics instruction should be designed to emphasize the effective use of digital learning resources, strengthen collaborative learning activities among students, and promote the development of self-regulated learning practices throughout the learning process.